Experimental investigation on location of debris impact source based on acoustic emission. Issue 11 (1st December 2019) - Tang, E.L.; Liang, Z.Q.; Wang, L.; Han, Y.F.
Abstract: In view of the objective reality that it takes a long time for debris to locate the impact point when debris impacts the spacecraft bulkhead, timely and accurate determination of the location of the impact source is the premise and basis for damage repair, which is of great significance to the safety of astronauts. In this paper, the experiments of 2A12 aluminium plate impacted by 2A12 aluminium projectile under different impact parameters have been performed by using the self-built acoustic emission testing system and two-stage light gas gun loading system. The calculated coordinates are compared with the experimental coordinates by using triangular positioning method, quadrilateral positioning method and acoustic emission (AE) signal processing method based on Wavelet transform. The experimental results show that the positioning accuracy of quadrilateral positioning method is better than that of triangular positioning method, and the acoustic emission signal processing method based on wavelet transform is obviously better than that of quadrilateral positioning method.